Analysis of Alkali Chemical Constituents from Holotrichia diomphalia Bates by GC-MS - Liu, Yuan-Yuan; Zhang, Ya; Cao, Wei; Wang, Si-Wang (Asian Journal of Chemistry, 2015)
The alkali chemical constituents were obtained after 95 % alcohol extraction, condensation, acidification and extraction with chloroform from Holotrichia diomphalia bates. The chemical constituents were analysis by GC-MS and their relative contents were calculated by area normalization method. Seventy nine components were identified and 14 nitrogen-containing compounds were found by analysis with GC-MS. The main of nitrogen-containing compounds including 2-piperidinone, 4-methyl-5-thiazoleethanol, 2-[4-(2-hydroxy-phenyl)-thiazol-2-yl]-5-phenyl-penta-2,4-dienenitrile, 4,4'-bis(dimethylamino)benzhydrol, 5a-pregnane-3,20a-dio,14a,18a-[4-methyl-3-oxo-(1-oxa-4-azabutane-1,4-diyl)]-diacetate, 5,10-diethoxy-2,3,7,8-tetrahydro-1H,6H-dipyrrolo[1,2-a:1',2'-d]pyrazine; 9H-pyrido[3,4-b]indole, 5-aminovaleric acid, Ile-ser, 4,4-dimethylazetidin-2-one and 1-methyl-2-piperidinone. The novel findings of the present study provide a scientific basis for the further development and utilization of Holotrichia diomphalia bates.